Respiration-dependent calcium ion uptake by two preparations of cardiac mitochondria. Effects of palmitoyl-coenzyme A and palmitoylcarnitine on calcium ion cycling and nicotinamide nucleotide reduction state - Wolkowicz, Paul E. (1980)
Ca(2+) uptake and the effect of the uptake inhibitors palmitoyl-CoA and palmitoylcarnitine were examined in two preparations of dog cardiac mitochondria. Mitochondria prepared by using the Nagarse technique was 2.5-fold more active in respiration-dependent Ca(2+) uptake than were mitochondria isolated by using the Polytron procedure. Palmitoyl-CoA and palmitoylcarnitine inhibited Ca(2+) uptake in both preparations uncompetitively, with K(i,app) 0.4 and 20μm. Ca(2+)-uptake rates were related to, or influenced by, the concentration of mitochondrial reduced nicotinamide nucleotides, with uptake slowing as this concentration decreased. When most of the nicotinamide nucleotides was oxidized, Ca(2+) release and respiratory stimulation were observed. In the presence of Ruthenium Red and palmitoyl-CoA, oxidation of nicotinamide nucleotides was abolished and the time to Ca(2+) release was shortened corresponding to the time of onset of nicotinamide nucleotide oxidation in the absence of Ruthenium Red. The results suggest that NAD(P)H oxidation in the presence of rotenone was a consequence of Ca(2+) re-uptake and that net Ca(2+) release could be observed as reduced nicotinamide nucleotide concentrations declined. Although nicotinamide nucleotide oxidation occurred in the presence of rotenone, it was not linked in an apparent manner to acyl-group metabolism (palmitoylcarnitine was less effective than palmitoyl-CoA). Therefore either a by-pass of the rotenone block or a direct interaction of NAD(P)H with the Ca(2+)-uptake process was possible. Loss of NADH occurred before respiratory stimulation, and this loss may relate to decreased coupling efficiency at sites 2 and 3 of the respiratory chain, as suggested by others [Bhuvaneswaran & Wadkins (1978) Biochem. Biophys. Res. Commun. 82, 648–654].